CLINICAL CASE OF A PATIENT WITH ATRIAL FIBRILLATION COMPLICATED BY THROMBOEMBOLISM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Thromboembolic syndrome is dangerous for patients with atrial fibrillation (AF) in 8-15%. The most common source of thromboembolism in atrial fibrillation is the left atrial appendage [1]. The incidence of thrombus detection in the cavity of the left atrial appendage in AF is 15.2% in the absence of anticoagulant therapy and 1–8% in patients taking drugs of this group [1]. To date, the cause of the formation of blood clots in this localization, even against the background of anticoagulant therapy, is not reliably known.